Satisfactory Learning Opportunities for "multi-sensory learning" with Educational Software Systems - Chan, P.; Krishnaswamy, Girija (International Institute of Informatics and Systemics, 2012)
A number of studies have concluded that one of the best approaches to accelerate the learning process is to apply a ‘multi - sensory’ learning approach in which learners are provided with as many different learning styles as possible, facilitating the flow of information to the learners’ brains simultaneously and holistically. This process can be aided by the use of educational software. This paper attempts to identify an education software system that truly supports a ‘multi - sensory’ learning approach. Different multimedia/interactive features embedded within educational software can be designed to stimulate different learning styles. From a review of the literature, a number of multimedia/interactive features that stimulate learning styles have been identified in educational software systems. To adequately cover and facilitate the understanding of the roles of these multimedia/interactive features in stimulating learning styles, two architecture models of the human brain, namely the ‘Split - Brain’ and ‘Multiple Intelligences’ models, have been utilized in this paper.A survey based on a number of studies in educational software concluded that the Computer Based Training (CBT) Software System and the Mind Mapping (MM) System have been found to stand out above the others in their ability to design and apply a diverse range of multimedia/interactive features, thereby enabling learners to engage in a variety of learning styles. The survey also reveals that one or more multimedia/interactive features that were found to be applicable in one system were found to be not applicable in the other. Further investigation into those multimedia/interactive features that were found to be non applicable in either one or the other system, was conducted. It was found that these features play a significant role in stimulating certain learning styles and hence this paper concludes that neither CBT nor MM software systems have the capability to accommodate a truly ‘multi - sensory’ learning methodology.